Utilization of CRISPR-Mediated Tools for Studying Functional Genomics in Hematological Malignancies: An Overview on the Current Perspectives, Challenges, and Clinical Implications - Solayappan, Maheswaran; Azlan, Adam; Khor, Kang Zi; Yik, Mot Yee; Khan, Matiullah; Yusoff, Narazah Mohd; Moses, Emmanuel Jairaj (Frontiers in Genetics, 2022)
Haematologic malignancies (HM) are a group of neoplastic disease that are usually heterogenous in nature due to the complex underlying genetic aberrations in which collaborating mutations enable cells to evade checkpoints that normally safeguard it against DNA damage and other disruptions of healthy cell growth. Research regarding chromosomal structural rearrangements and alterations, gene mutations and functionality are currently being carried out to understand the genomics of these abnormalities. It is also becoming more evident that cross-talk between the functional changes in transcription and proteins give the characteristics of the disease although specific mutations may induce unique phenotypes. Functional genomics is vital in this aspect as it measures the complete genetic change in cancerous cells and seeks to integrate the dynamic changes in these networks to elucidate the various cancer phenotypes. The advent of CRISPR technology has indeed provided a superfluity of benefits to mankind, as this versatile technology enables DNA editing in the genome. The CRSIPR-Cas9 system is a precise genome editing tool and it has revolutionized methodologies in the field of haematology. Currently, there are various CRISPR systems that are used to perform robust site-specific gene editing to study HM. Furthermore, experimental approaches that are based on CRISPR technology have created promising tools for developing effective haematological therapeutics. Therefore, this review will focus on the diverse applications of CRISPR-based gene-editing tools in HM and its potential future trajectory. Collectively, this review will demonstrate the key roles of different CRISPR systems that are being used in HM and the literature will be a representation of a critical step toward further understanding the biology of HM and the development of potential therapeutic approaches.